2021
DOI: 10.1176/appi.ps.202000623
|View full text |Cite
|
Sign up to set email alerts
|

Telehealth Acceptability and Feasibility Among People Served in a Community Behavioral Health System During the COVID-19 Pandemic

Abstract: The authors examined the acceptability and feasibility of telehealth services shortly after their rapid introduction into a community behavioral health agency as part of the response to the COVID-19 pandemic.Methods: Individuals receiving services during May 8-18, 2020, from behavioral health programs that had introduced telehealth in March 2020, were invited to participate in a survey regarding their perceptions of the telehealth services. Ordinal logistic regressions were used to test for differences in surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 24 publications
1
30
0
Order By: Relevance
“…Adolescents appeared to prefer telehealth to in-person services delivery [32,33], and states with high rates of coronavirus positivity and high rates of unmet need were most likely to continue use of telehealth post-pandemic. Similar benefits have been reported in studies of use of telehealth to deliver mental health services to adults by primary care providers [34] and specialty mental health care providers [35] during the pandemic.…”
Section: Discussionsupporting
confidence: 73%
“…Adolescents appeared to prefer telehealth to in-person services delivery [32,33], and states with high rates of coronavirus positivity and high rates of unmet need were most likely to continue use of telehealth post-pandemic. Similar benefits have been reported in studies of use of telehealth to deliver mental health services to adults by primary care providers [34] and specialty mental health care providers [35] during the pandemic.…”
Section: Discussionsupporting
confidence: 73%
“…It can also make healthcare use more convenient for many individuals, and some healthcare professionals are expected to continue to use telehealth post-COVID-19 ( Zhu et al, 2021 ). For those with behavioral healthcare needs, telehealth is not only acceptable but a preferred service delivery mode because of its convenience ( Tse et al, 2021 ). Our findings indicate that solutions for closing the digital divide and increasing telehealth use among older adults are readily achievable with access to ICT devices and the internet and lessons on how to use technology, especially for low-income older adults.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to COVID-19, an umbrella review of the implementation of telehealth in mental health services found that outcomes appear comparable with face-to-face interventions with similar effectiveness and participant adherence, good therapeutic alliance and high patient satisfaction. 10 However, the umbrella review found discrepancies with reported cost-effectiveness. One review found sixty percent of studies indicated telehealth to be less expensive than face-to-face care due to reduced travel time and need for patients and their families to take time off work.…”
Section: Effectiveness and Costmentioning
confidence: 99%